The Determinants Of Audit Fees For Smes In Malaysia And Implications Of Mia Guidlines - Kasim, Mohd Nizam (2005)
To date, there has been little work done on developing countries especially issues on auditor independence, audit quality, audit delays, and audit fee determinants. Even more scarce is studies on audit and Small and Medium Enterprises (SMEs). As such, this paper is to address this imbalance by having a closer look on audit fee determination of SMEs in Malaysia.